Non-Dependent and Dependent Daily Cannabis Users Differ in Mental Health but Not Prospective Memory Ability - Braidwood, Ruth; Mansell, Samantha; Waldron, Jon; Rendell, Peter G.; Kamboj, Sunjeev K.; Curran, H. Valerie (Frontiers in Psychiatry, 2018)
Research suggests that daily cannabis users have impaired memory for past events, but it is not clear whether they are also impaired in prospective memory (PM) for future events. The present study examined prospective memory in daily cannabis users who were either dependent (n = 18) or non-dependent (n = 18), and compared them with non-using controls (n = 18). The effect of future event simulation (FES) on PM performance was also examined. Participants were matched across groups on age, gender, and highest level of education. The Virtual Week was used to objectively assess PM abilities, both at baseline and following FES. Other measures used were: cannabis use variables, immediate and delayed prose recall, phonemic and category fluency, Spot-the-Word test (pre-morbid intelligence), Beck Depression Inventory (BDI-II), Beck Anxiety Inventory (BAI), and a measure of schizotypy (O-LIFE: Unusual Experiences subscale). No group differences were found in PM performance on the Virtual Week, and FES did not improve PM performance in any group. Dependent cannabis users scored higher on depression, anxiety and schizotypy than both other groups with non-dependent cannabis users scoring at a similar level to controls. There were no group differences in alcohol use. Findings suggest that when carefully matched on baseline variables, and not differing in premorbid IQ or alcohol use, young, near-daily cannabis users do not differ from non-using controls in PM performance.